2023
DOI: 10.1111/pai.13926
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum allergen‐specific immunoglobulin E and threshold dose in an oral food challenge

Abstract: The prevalence of food allergies is increasing globally. 1 Although strict avoidance is mandatory for severe food allergies, accidental ingestion frequently occurs. 2 The frequency of accidental ingestion depends on an individual's threshold for food allergens. 3 An individual's threshold provides information on the maximum tolerable doses and minimum eliciting doses. 4 Although studies have revealed threshold doses for different allergens, 4-8 evidence regarding risk factors for a low threshold dose is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…A systematic review of the OFC in Japan suggested that the OFCs for egg and milk help avoid complete elimination [33,34]. Japanese guidelines recommend a stepwise OFC (Table 2) [3,27,35], which is widely practiced. A stepwise OFC allows the determination of the food amount that can be ingested [3,27].…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review of the OFC in Japan suggested that the OFCs for egg and milk help avoid complete elimination [33,34]. Japanese guidelines recommend a stepwise OFC (Table 2) [3,27,35], which is widely practiced. A stepwise OFC allows the determination of the food amount that can be ingested [3,27].…”
Section: Key Pointsmentioning
confidence: 99%
“…Japanese guidelines recommend a stepwise OFC (Table 2) [3,27,35], which is widely practiced. A stepwise OFC allows the determination of the food amount that can be ingested [3,27]. Mitomori et al [36 & ] performed a stepwise OFC for infants sensitized to hen's eggs with no history of immediate symptoms and were able to stratify the egg allergy according to the threshold level.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…
Oral food challenge (OFC) tests are necessary in food allergy practice. [1][2][3][4] The spread of the Omicron variant of severe acute respiratory syndrome coronavirus 2 significantly affected food allergy practice. 5,6 Universal pre-admission screening for coronavirus disease 2019 (COVID-19) may effectively identify patients with asymptomatic COVID-19.
…”
mentioning
confidence: 99%